Triglyceride-glucose index predicts death in patients with stroke younger than 65 - Liu, Ruishan; Li, Lijuan; Wang, Lu; Zhang, Shihong (Frontiers in Neurology, 2023)
Background: The triglyceride-glucose index (TGI), a reliable surrogate indicator of insulin resistance (IR), has been proven to be a predictor of the incidence of ischemic stroke. The role of TGI in predicting the outcomes of stroke patients remains controversial. Susceptibility to IR-related diseases varies among patients of different ages. The study aims to evaluate the predictive value of TGI levels on clinical outcomes of patients with ischemic stroke of different ages.Method: This was a retrospective cohort study including patients with ischemic stroke in the Department of Neurology at West China Hospital. TGI was calculated as ln [fasting triglyceride (mg/dL)×fasting glucose (mg/dL)/2]. The patients were subdivided into 3 tertiles according to TGI levels. Multivariate logistic regression analyses were conducted to estimate the association between TGI levels and post-stroke outcomes among the whole patients, younger patients (<65) and older patients (>=65). The outcomes included death and unfavorable functional outcome (modified Rankin scale score 3-6) at 3 and 12 months after stroke.Results: A total of 3704 patients (men, 65.08%, mean age, 61.44±14.15; women 34.92%, mean age, 65.70±13.69) were enrolled in this study. TGI levels were not associated with 3-month or 12-month death in the whole patients. Patients with higher TGI levels (T2 and T3) had a higher risk of 3-month death than those had lower TGI levels (T1) in the younger group (T2 vs. T1: OR 2.64, 95% CI 1.03-6.79, p=0.043; T3 vs. T1: OR 2.69, 95% CI 1.00-7.10, p=0.049) but not in the older group.Additionally, Kaplan-Meier estimate analysis illustrated that the 12-month death risk was significantly higher in the group with the highest TGI among younger patients (p for log-rank